2019
DOI: 10.1371/journal.pone.0218475
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid and chondroitin sulfate, alone or in combination, efficiently counteract induced bladder cell damage and inflammation

Abstract: Interstitial cystitis and/or bladder pain syndrome (IC/BPS) are characterized by discomfort, abdominal pain, and pelvic pain, and they are often associated with chronic diseases. Pathological conditions related to IC/BPS can occur due to a defect in the integrity of the bladder lining. This defect has been ascribed to damage to the glycosaminoglycan (GAG) layer of the urinary epithelium. In addition, the incipient cascade of inflammation events might prompt extracellular matrix degradation. Several medical dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…The results showed a significant reduction of edema (in the absence of radiographic changes), knee pain, improved knee flexion, and an increase in walking time. The composition of the extract was determined by HPLC [ 36 ] (boswellic acid 40%, the main potential active ingredient (3- O -acetyl-11-keto-beta-boswellic acid) only 2%). In another study, patients were administered the drug (5-loxin, enriched with Boswellia serrata extract with 30% AKBA) in two doses: 100 mg/day and 250 mg/day.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed a significant reduction of edema (in the absence of radiographic changes), knee pain, improved knee flexion, and an increase in walking time. The composition of the extract was determined by HPLC [ 36 ] (boswellic acid 40%, the main potential active ingredient (3- O -acetyl-11-keto-beta-boswellic acid) only 2%). In another study, patients were administered the drug (5-loxin, enriched with Boswellia serrata extract with 30% AKBA) in two doses: 100 mg/day and 250 mg/day.…”
Section: Resultsmentioning
confidence: 99%
“…A group of scientists studied three doses of MSCs from adipose tissue (2 × 10 6 , 10 × 10 6 , 50 × 10 6 of cells) [ 35 ]. It is also believed that MSCs can work through innate and adaptive immune modulation [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several clinical studies have shown the efficacy of intravesical instillation of high concentrations of sodium hyaluronate and sodium CS in protecting the urothelium in different settings [12] , [13] , [14] , [15] . Considering the positive results obtained for intravesical HA and CS instillation for the treatment of bladder diseases such as urinary tract infections and bladder pain syndrome, which symptomatically resemble radiation-induced cystitis, we reasoned that protection of the urothelium by HA and CS during RT could represent a preventive strategy capable of alleviating the consequences, hence avoiding or improving the symptoms of radiation-induced cystitis and improving QoL.…”
Section: Introductionmentioning
confidence: 99%
“…For example, exogenous GAGs reduce the production and activity of proinflammatory mediators and matrix metalloproteinases in chondrocytes under inflamed conditions. In a recent in vitro study under a bladder model system, TNFα was used to mimic IC/BPS damage in the bladder (Stellavato et al, 2019a). In this study both exogenous HA, CS, and combination were anti-inflammatory.…”
Section: Discussionmentioning
confidence: 98%
“…Intravesical treatment options for IC/BPS offer a number of advantages over oral administration including the ability to administer high concentrations of therapeutic agent directly to the affected site in the bladder, and a lower likelihood of systemic side effects (Kaufman et al, 2010). There is very limited in vitro data comparing the various treatment options available (Gülpınar et al, 2018;Stellavato et al, 2019a). Comparative studies at the cellular and molecular level can lead to better understanding of the pathology and may help identify promising targets for future treatments.…”
Section: Discussionmentioning
confidence: 99%